(x+9)2-100=0

Simple and best practice solution for (x+9)2-100=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+9)2-100=0 equation:


Simplifying
(x + 9) * 2 + -100 = 0

Reorder the terms:
(9 + x) * 2 + -100 = 0

Reorder the terms for easier multiplication:
2(9 + x) + -100 = 0
(9 * 2 + x * 2) + -100 = 0
(18 + 2x) + -100 = 0

Reorder the terms:
18 + -100 + 2x = 0

Combine like terms: 18 + -100 = -82
-82 + 2x = 0

Solving
-82 + 2x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '82' to each side of the equation.
-82 + 82 + 2x = 0 + 82

Combine like terms: -82 + 82 = 0
0 + 2x = 0 + 82
2x = 0 + 82

Combine like terms: 0 + 82 = 82
2x = 82

Divide each side by '2'.
x = 41

Simplifying
x = 41

See similar equations:

| 3x-70=x | | 7x+5(1x+-1)=5+12x | | 7p-3=p+6 | | -5(t-2)+9t=6t-2 | | 4x+5y+7x+3y= | | (x-5)2-16=0 | | 3(4x-8)+1=12x-23 | | k+5=3-w | | 3x=-5y+4 | | -3+2=-10+3x | | 3.6+x=4.9 | | 8.21m=49.26 | | 4x+7=4(x+3) | | (x-2)2=144 | | -6(-7x-5)-2x=-1 | | 61+2x= | | 45+4x= | | -(1+7)-(-7-x)=36 | | -3(7+g)=9 | | 9114=93k | | 5(x-7)-3=-38 | | 3n+(12-5n)=22 | | 2/5-9=4 | | 4x^2-17x+25=3x+4 | | x=18.2-.4y | | (x+6)2=36 | | 6.5(-4)+4=-22 | | 2x-4=(x+10) | | (x+1)2=81 | | 11y=1 | | 9=53/5 | | 9(7b+4)=9(1+4b) |

Equations solver categories